2017
DOI: 10.1007/s00330-017-4978-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging-Detected Extramural Venous Invasion in Rectal Cancer before and after Preoperative Chemoradiotherapy: Diagnostic Performance and Prognostic Significance

Abstract: • Diagnostic performance of MRI for EMVI after preoperative chemoradiotherapy is good. • The mean DFS was lower in yMR-EMVI-positive than yMR-EMVI-negative patients. • MRI can facilitate prognosis prediction of rectal cancer patients with preoperative chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 23 publications
5
43
0
1
Order By: Relevance
“…Based on multivariate analysis, only post-CRT MRI features such as EMVI post (HR, 2.259; p = 0.048) for OS and extramesorectal LN (HR, 2.610; p = 0.008) and EMVI post (HR, 5.011; p < 0.001) for DFS were the significant MR parameters in predicting patients' prognosis. These observations were well in line with those of the previous studies ( 30 ) and our common belief. This is likely because treatment response to CRT may vary among patients, and it is generally difficult to predict the responsiveness before treatment.…”
Section: Discussionsupporting
confidence: 94%
“…Based on multivariate analysis, only post-CRT MRI features such as EMVI post (HR, 2.259; p = 0.048) for OS and extramesorectal LN (HR, 2.610; p = 0.008) and EMVI post (HR, 5.011; p < 0.001) for DFS were the significant MR parameters in predicting patients' prognosis. These observations were well in line with those of the previous studies ( 30 ) and our common belief. This is likely because treatment response to CRT may vary among patients, and it is generally difficult to predict the responsiveness before treatment.…”
Section: Discussionsupporting
confidence: 94%
“…5 Various studies have shown a wide range of MRI sensitivity (28-90%) and specificity (41-94%) for detection of EMVI. 2,3,6,7 Since the time of EMVI's introduction for rectal cancer with MRI, the accuracy of pre-operative assessment has been known to be approximately 70-80% at best. 2,3,7,8 Lim et al reported diagnostic-predictive values of MRI in identifying EMVI in primary rectal cancer; specifically, the sensitivity, specificity and accuracy were 28, 94, and 80%, respectively.…”
mentioning
confidence: 99%
“…Therefore, the European Society for Medical Oncology guidelines suggest that mrEMVI indicates high risk; CRT followed by TME is recommended in such cases [24]. Moreover, several studies have shown that the presence of ymrEMVI, which was evaluated after the neoadjuvant treatment, and not only mrEMVI, had prognostic impact [23,[25][26][27]. Our study revealed that mrEMVI remained after NAC except for 2 patients.…”
Section: Discussionmentioning
confidence: 59%